PENGARUH VARIABEL MAKRO EKONOMI TERHADAP INDEKS SAHAM DI JAKARTA ISLAMIC INDEX (JII) (Periode 2012-2016) - Arif Afendi (FE Program Studi Manajemen, 2017)
The purpose of this research is to analyze the influence of macroeconomicfactor includes inflation rates, Rupiah current exchange rate, interest rates of BankIndonesia, and the price of gold to the Syariah stock index which is Jakarta IslamicIndex (JII). The sample collection technique has been done by using purposivesampling. The samples are 60 JII Indexes from 2012 to 2016. The secondary datawhich has been done by using documentation method in the form of statistics data andindex summary of 2012-2016 periods which has been obtained from Bank Indonesia,Bloomberg and Indonesia Stock Exchange (IDX). The data was analysis by usingmultiple linear regressions analysis. The result of the research shows that :1. Theinflation rates has negative but not significant influence to the Jakarta Islamic Index(JII), 2. Rupiah current exchange has positive and significant influence to the JakartaIslamic Index (JII) , 3. The interest rates of Bank Indonesia has negative andsignificant influence to the Jakarta Islamic Index (JII), and 4. The price of gold haspositive and significant influence to the Jakarta Islamic Index (JII).Keywords: inflation rates, Rupiah current exchange rate, interest rates of BankIndonesia, the price of gold, and Jakarta Islamic Index (JII)